Chemotherapy for metastatic colon cancer: No effect on survival when the dose is reduced due to side effects - Munker, Stefan; Gerken, Michael; Fest, Petra; Ott, Claudia; Schnoy, Elisabeth; Fichtner-Feigl, Stefan; Wiggermann, Philipp; Vogelhuber, Martin; Herr, Wolfgang; Stroszczynski, Christian; Schlitt, Hans Juergen; Evert, Matthias; et al. (BMC Cancer, 2018)
Background: 5-Fluorouracil (5FU), Folinic acid (FA), and Oxaliplatin (FOLFOX) or 5FU, FA, and Irinotecan (FOLFIRI) are standard regimens for palliative chemotherapy of metastatic colon cancer. Since data showing the influence of dose reduction in palliative treatment are rare, the objective of this single center, retrospective study was to further characterize the influence of dose reduction on efficacy of these therapeutic regimens. Methods: One hundred nine patients, diagnosed with stage IV colon cancer between 2004 and 2012 and receiving palliative first-line chemotherapy with either FOLFOX or FOLFIRI regimens in our outpatient clinic were analyzed for treatment efficacy. Patients who received dose reductions due to side effects usually received doses of 80% or lower of per protocol dose. Survival data were obtained from the Regensburg Tumor Registry. Survival analysis was performed using Kaplan-Meier statistical analysis and multivariable analysis. Results: A dose reduction due to side effects was necessary in 46 (42%) patients. Dose reduction was independent of age. Major reasons for dose reduction were neutropenia (30%) followed by polyneuropathy (16%) and diarrhea (14%). Dosage was more often reduced in patients receiving FOLFOX based therapy. Comparison of patients with dose reduction versus patients with full dosage showed no significant difference on overall survival (p = 0.430). Subgroup analysis revealed dose reduction in patients with N2 stage disease was associated with improved survival. Patients who underwent dose reduction received more cycles of chemotherapy (13.7 vs. 10.8 cycles) and cumulative dosage was similar in both groups. Conclusion: Contrary to our expectations, the need to reduce chemotherapy dosage due to side effects does not indicate a worse prognosis in our retrospective analysis. We believe this can in part be explained by better adaption to interindividual pharmacokinetics and longer time of treatment.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Cancer; Chemotherapy; Colorectal cancer; Dose reduction